Lower limbs inter-joint coordination and variability during typical Tai Chi movement in older female adults - Zhao, Jianmin; Han, Wei; Tang, Huiru (Frontiers in Physiology, 2023)
Purpose: This study aimed to investigate the lower limb inter-joint coordination and variability during Tai Chi movements compared with normal walking in older adults. Methods: A total of 30 female Tai Chi practitioners (70.9 ± 5.2 years) were recruited in this study. Herein, each participant performed three trials of the normal walking and Tai Chi movements. The lower limb kinematics data were collected with Vicon 3D motion capture system. The continuous relative phase (CRP) includes both spatial and temporal information of two adjacent joints, which was calculated to assess the inter-joint coordination of lower limbs. Coordination amplitude and coordination variability were assessed with mean absolute relative phase (MARP) and deviation phase (DP). MANOVOA was used to analyze inter-joint coordination parameters between different movements. Results: The CRP values of hip-knee and knee-ankle segments in the sagittal plane of the Tai Chi movements changed frequently. The MARP values of the hip-knee (P < 0.001) and knee-ankle segments (P = 0.032) as well as the DP values of the hip-knee segment (P < 0.001) were significantly lower in Tai Chi than in normal walking. Conclusion: More consistent and stable inter-joint coordination patterns of Tai Chi movements found in this study may be one of the critical factors that Tai Chi could be a suitable coordinated exercise for older adults.